Using Artificial Insemination Technology in Goats - Tambing, Surya Natal; Gazali, Muhamad; Purwantara, Bambang (Indonesian Animal Sciences Society, 2001)
In general, local goat productivity in Indonesia is relatively still lower than that from the temperate area. Yearling body weight in local goat about 14-17 kg. However, the local goat have superiority, such as adaptability and a good reproductive performance, which have litter size 1,49-1,61. Increasing local goat productivity may be done by breeding program (cross breeding and selection) and the environmental improvement. Both cross breeding program and selection that involve mating regulation will be efficient by reproductive technology application, such as artificial insemination (AI). Application of AI in goats is limited by four main factors that influence simultaneously, viz. poor quality of frozen semen, the variety of female reproductive performance, improper technical and insemination time, and poor management. To overcome these constraints his obligatory to pay more attention, so that AI will be able to be used as one of tools to increase the population and genetic quality in goats. Â Key words: Goat, reproductive efficiency, artificial insemination